Serial Changes in the Coagulation System Following Clotting Factor Concentrate Infusion - Preston, F. E; Winfield, D. A; Malia, R. G; Blackburn, E. K (Thrombosis and Haemostasis, 1975)
Various parameters of the coagulation system have been monitored in patients with Christmas disease following the infusion of clotting factor concentrates. Significant reduction of clotting factor VIII and serum antithrombin III were observed in each of the five studies, whilst the plasma fibrinogen level fell in four subjects. The induced abnormalities were shortlived and there were no clinical sequelae. Further studies are required to assess the effects of similar concentrates in patients with liver disease.